2019
DOI: 10.1016/j.foodres.2018.08.019
|View full text |Cite
|
Sign up to set email alerts
|

Thermal and irradiation resistance of folic acid encapsulated in zein ultrafine fibers or nanocapsules produced by electrospinning and electrospraying

Abstract: The objectives of this study were to characterize zein fibers and capsules prepared by electrospinning and electrospraying techniques, respectively, and then use them to encapsulate folic acid. Folic acid containing fibers and capsules (0.5, 1.0, and 1.5%, w/v) were submitted to thermal treatment (100, 140, and 180°C) and ultraviolet A light (UVA) irradiation to evaluate the resistance of folic acid. Zein fibers and capsules containing folic acid showed high encapsulation efficiency (> 80%). Unencapsulated fol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
33
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 57 publications
(39 citation statements)
references
References 41 publications
4
33
2
Order By: Relevance
“…Similar studies that have reported distances of 10 cm for zein nanoparticles were those of do Evangelho et al. () and Gómez‐Mascaraque et al. ().…”
Section: Resultssupporting
confidence: 84%
See 3 more Smart Citations
“…Similar studies that have reported distances of 10 cm for zein nanoparticles were those of do Evangelho et al. () and Gómez‐Mascaraque et al. ().…”
Section: Resultssupporting
confidence: 84%
“…Studies report that needle distance of the collector and solvent evaporation exert a significant impact on particle size and distribution with three behaviors as follows: the first behavior, were at short distance (<10 cm) and high solvent evaporation, a smaller diameter is obtained; the second, if the collector distance is very short (5 cm), it will not be possible to evaporate all of the solvent; thus, the particle will be unstable and the size will be larger (Costamagna et al, 2017;Ghayempour, & Mortazavi, 2013), and, in the third behavior, if the collector distance is long (>10 cm) with low solvent evaporation, it can volatilize the solvent and the polymer particle encourages fission Tapia-Hernández et al, 2017). Similar studies that have reported distances of 10 cm for zein nanoparticles were those of do Evangelho et al (2018) and Gómez-Mascaraque et al (2018).…”
Section: Food Engineering Materials Science and Nanotechnologymentioning
confidence: 52%
See 2 more Smart Citations
“…The suspension obtained from the previous section was pumped at a flow rate of 1 ml/h by an infusion pump to a 16‐gauge blunt end stainless steel needle that acted as a spinneret, in accordance with the methodology described by Evangelho et al () for capsules production with some modifications. The spinneret was connected to the positive electrode of a 20 kV direct current power supply.…”
Section: Methodsmentioning
confidence: 99%